Hadith #6651 - Sahih Muslim - al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري (Sahih Muslim)
Had Allah’s Messenger (ﷺ) not stated this..” None should make a request for death,” I would have definitely done that.
Grade: Sahih